High blood pressure is correlated with anthropometric status in adults in Gribig district, Central Java, Indonesia - Anandita Anughrayasa, emmanuela; budiartanti, eviana; Christanti, Jessica (World Nutrition Journal, 2024)
Background: More than 17 million deaths worldwide are caused by cardiovascular disease due to high blood pressure. According to the World Health Organization (WHO), around 1.3 billion adults will have high blood pressure in 2021. Obesity is a significant factor influencing blood pressure. Waist circumference measurements and body mass index (BMI) can be used to identify obesity issues. Objective: The aim was to analyze the correlation between BMI, waist circumference, and blood pressure among adults at Primary Health Care in Kudus, Central Java, Indonesia. Methods: This cross-sectional study evaluated BMI, waist circumference, blood pressure, and questionnaire. Men and women aged 18-59 (healthcare staff, patient caregivers, and patients) who agreed to become study subjects were included. Participants with a history of diseases, current conditions, medication intake that affects blood pressure, and pregnancy were excluded. Samples were taken using purposive sampling and the Pearson test as a statistical analysis. Results: The analysis showed a significant correlation between the BMI of patients with systolic blood pressure (p=0.000) and diastolic blood pressure (p=0.000). A moderate relationship was found between BMI and systolic blood pressure(r=0.473) and diastolic blood pressure (r=0.439). Moreover, waist circumference was significantly correlated with systolic blood pressure (p=0.000) and diastolic blood pressure (p=0.000). Conclusion: A significant correlation exists between BMI and waist circumference with blood pressure among adults at the Primary Health Care in Kudus, Central Java, Indonesia.